Brain volumes are related with motor skills at late childhood in children born extremely preterm - Lina Broström; Hedvig Kvanta; Maria Örtqvist; Nelly Padilla; Ulrika Ådén (PLoS ONE, 2025)
Background This study had three aims. First, we wanted to explore if there was difference in motor performance at 12 years of age in children born extremely preterm (EPT < 28 weeks of gestation) and at term. Our second aim was to study whether the volumes of motor networks and regions differed between those groups when they underwent brain scans at 10 years of age. Third, we investigated whether there were differences in the motor networks and regions of the brain in children born EPT who did or did not have motor impairment at 12 years of age. Methods In a Swedish national study, a subgroup of 42 children born before 27 weeks and 25 term-born controls underwent MRI at age 10. A neuroradiologist performed MRI acquisitions, and analyses focused on brain regions associated with motor function. At age 12, motor function was assessed using the Movement Assessment Battery for Children – Second Edition (MABC-2), conducted by a licensed physiotherapist. Examiners were blinded to group status. Motor function and motor-related brain volumes were compared between the EPT and control group, and between children born EPT with and without motor impairments. Results Findings revealed significantly reduced motor performance and smaller motor region volumes in EPT children compared to controls (p < 0.001). Among EPT children, those with motor impairment especially in aiming and catching, had notably smaller brain volume in the basal ganglia (mean difference:1.2 cm3, p = 0.049), cerebellum (mean difference:14.4 cm3, p < 0.001), motor execution (mean difference:3.7 cm3, p = 0.049) network and motor imagery network (mean difference 5.6 cm3, p = 0.049) than their EPT peers without such impairments. Cerebellar volume remained significant different between the groups when adjusting for birth weight and sex in a linear regression model, p = 0.02 (η2 = 0.17). Conclusion The results underscore the impact of extreme prematurity on motor function and brain structure, highlighting a specific link between reduced motor area volumes and impaired ball skills.